Delayed ileostomy closure increases the odds of Clostridium difficile infection. (14th August 2021) - Richards, Simon J. G.; Udayasiri, Dilshan K.; Jones, Ian T.; Hastie, Ian A.; Chandra, Raaj; McCormick, Jacob J.; Chittleborough, Timothy J.; Read, David J.; Hayes, Ian P.
Abstract: Aim: A diverting ileostomy is typically performed to divert intestinal contents in high‐risk colorectal anastomoses. Ileostomy closure is associated with high rates of postoperative Clostridium difficile infection (CDI). Risk factors for the development of CDI are unclear; however, a correlation has been observed with delayed closure. This study aimed to assess the odds of developing CDI in patients who had a delay to reversal of ileostomy, compared to those who had no delay. Methods: A retrospective cohort study was conducted of patients undergoing reversal of ileostomy between 2010 and 2019 at a single tertiary centre. A delay to reversal of ileostomy was defined if the procedure was performed at >365 days following the index procedure. CDI was defined as the presence of Clostridium difficile toxin associated with diarrhoea. Univariable logistic regression analysis was performed to estimate odds of CDI for each covariable, comparing patients who had a delay to reversal of ileostomy with those who did not. Multivariable logistic regression analysis was used to adjust for the potential confounding effects of covariables. Results: Of 195 patients, 11 (5.6%), developed postoperative CDI. Multivariable analysis showed that delay to reversal of ileostomy was associated with a nearly 7‐fold increase in odds of CDI (OR = 6.95, CI: 1.06–81.6; p ‐value = 0.03). Conclusion: A delay to reversal of ileostomy of >365 days was associated with a higher incidence of CDI postoperatively. Careful consideration should be given to the timing of reversal and appropriate preoperative counselling of patients.